CLAIMS AND MODEL OF PRIMARY STRATEGY AND TRANSPARENCY IN THE MUNICIPAL SAVINGS AND CREDIT BANK OF ICA S.A., PERU - Huailla-Calle, Nellida Tania (2022)
The aim of the study was to describe the number of claims and to propose a model of strategy and primary transparency in the Caja Municipal de Ahorro y Crédito de Ica S.A, Perú. The study was carried out between June and July 2022. The number of claims between the 2017-2021 period is described. The number of complaints increased each year: 301, 427, 479, 528, and 558 together with the number of clients: 198440, 229103, 261306, 257290, and 278798. A statistically significant difference was found in the two variables where the correlation coefficient was higher. The equation of the adjusted model was: Number of Claims = -303.814 + 0.00311205*Number of clients. In the case of the strategy and primary transparency model, the following variables were proposed: type of operations, contractual documents, description (objective and rationale) and dynamic understanding of the information. It is concluded that the number of claims was increasing and is related to the increase in customers. Likewise, the proposal of the strategy and primary transparency model as a practical tool and with a tangible attribute allows the recognition of consumers towards the financial product and service of the Caja Municipal de Ahorro y Crédito de Ica S.A. Keywords: consumers – financial competence – financial service – identity model – microenterprise – strategy